From labor to work: re-engaging human-scale participation through recreation and making in a semi-autonomous society - Deletic, Danilo (My University, 2021)
The world we live in is at a crossroads. The ever-widening wealth gap is creating a grotesque, top heavy caricature of our current economic system. The choices we make in the coming decade will set the scene for the long term future. This report focuses on the more optimistic approach, where the potential for basic needs becoming a fundamental right, through schemes such as a Universal Economic Distribution System, is a reality. The advent of autonomous systems in the work force and the distribution of the Internet of Things to all stretches of the globe make this all the more reaIistic and relevant. The theoreticaI focus of this report is to understand the implications and unintended consequences of a Semi-Autonomous society and its systems, where the vast majority of citizens are no longer needed for their previous labor participation. Considering the current state of unemployment in South Africa, destined to rise exponentially with the implementation of these systems, it is imperative that a viable plan of action be established to curtail the loss of meaning to the citizens of our country. With the fast paced development of autonomous and digital technologies, uninterrupted connection will become the norm. In an overly connected world there will be a requirement for spaces of disconnection. To provide the opportunity and space for this disconnection, a purpose for reconnection to the human-scale must be established. The inspiration for this purpose is drawn from Abraham Maslows' theories on needs motivation. Understanding the psychological motivation of our species can be used to inform the future architectural devices that can engage human-scale participation. ArchitecturaIly this report questions traditionaI ideologies and typologies that engage the human mind and body, to unify the two and develop a new typology for the Semi-Autonomous society. The Vitruvian concepts of strength, function and beauty are superimposed with the ancient Greek agora, speculative projects like the "No-Stop city" and anarchist works of architecture that empower communities and promote human-scale interaction. The typology that this report proposes is an Adaptable Urban Communal Sanctuary; communal interventions are set up to provide an alternative to the mass produced autonomous machine of the future. Human-scale work is provided as recreation to serve both a communal and self fulfilling function; Taking into consideration future proofing architectural concepts that make the intervention of today viable within a Semi-Autonomous future. The project is situated in the city of Johannesburg within the Corridors of Freedom urban development framework, and located on the corner of Empire Drive and Barry Hertzog Avenue. The principles of the Corridors of Freedom initiative closely align with the principles drawn through the theoretical investigations of this study. The rich history of making and human-scaleactivities in the immediate context provide the opportunity for a project that provides the required activities and spaces to engage an idle society, while simultaneously integrating itself into the urban fabric
A research report submitted to the School of Architecture and Planning, Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Architecture (Professional), 2021